Channel estimation method for multi-node amplify-and-forward co-operative communication over frequency-selective fading channels - YAN Kai; DING Sheng; ZHU Ming-hua; LIU Hai-tao (Tongxin xuebao)
A training sequence aided least squares channel estimation method was proposed for orthogonal frequency di-vision multiplexing （OFDM） based multi-node amplify-and-forward （AF） cooperative communication over fre-quency-selective fading channels. The mean square error bound on the proposed method is derived and the optimal train- ing sequence scheme with respect to this bound is also given. In addition, Chu sequence with the optimal power alloca- tion is chosen as training sequence to achieve the minimum mean square error estimation performance. Simulation results confirm the performance of the proposed channel estimation method in multi-node AF cooperative communication sce- narios and the superiority of the derived optimal training sequence scheme.